Aseptic Technique. Issue 1 (9th March 2020) - Bykowski, Tomasz; Stevenson, Brian
Abstract: This article describes common laboratory procedures that can reduce the risk of culture contamination (sepsis), collectively referred as "aseptic technique." Two major strategies for aseptic work are described: using a Bunsen burner and using a laminar flow hood. Both methods are presented in the form of general protocols applicable to a variety of laboratory tasks such as pipetting and dispensing aliquots, preparing growth media, and inoculating, passaging, and spreading microorganisms on petri dishes. © 2020 by John Wiley & Sons, Inc.